Analisis Faktor-Faktor yang Berhubungan dengan Kepuasan Pasien Rawat Jalan RSUD Kudungga - Marinda, Indri; Adrianto, Ratno (Jurnal Kesehatan Komunitas, 2025)
Medical services are assessed through indicators that gauge patient satisfaction with the services rendered by hospitals, contingent upon the quality of those services. Numerous complaints from the public regarding Kudungga Hospital persist. This study seeks to analyze the factors influencing outpatient treatment satisfaction at Kudungga Hospital. A cross-sectional approach is employed in the study, utilizing a quantitative methodology. Independent variables include access, admission process, waiting time, physical environment, doctor consultation, information for patients and the dependent variable is outpatient satisfaction. The population is outpatients at Kudungga Hospital in December 2023 as many as 3373 people. The sample technique was purposive sampling technique and through Slovin calculation there were 358 respondents as samples in this study. The research analysis used Spearman Rank and multiple logistic regression. The results showed that the factors associated with employee performance at Puskesmas were access (0.0001), admission process (0.0001), waiting time (0.0001), physical environment (0.015), doctor consultation (0.0001), information for patients (0.0001). The dominant variable was the admission process with 5.24 (95% CI OR = 2.585-10.656). The conclusion is that patient satisfaction will be high if the services provided are good starting from reception officers, hospital facilities, health workers and access to health care facilities. It is recommended that hospital management evaluate the quality of hospital services through suggestions and criticisms from patients who seek treatment.